Pulse Discharging of Sodium-Oxygen Batteries to Enhance Cathode Utilization - Daniel Langsdorf; Timo Dahms; Valerie Mohni; Julian Jakob Alexander Kreissl; Daniel Schröder (Energies, 2020)
Using sodium metal in sodium-oxygen batteries with aprotic electrolyte enables achieving a very high theoretical energy density. However, the promised values for energy density and capacity are not met in practical studies yet due to poor utilization of the void space in the cathode during battery discharge. In this work, we achieve better cathode utilization and higher discharge capacities by using pulse discharging. We optimize the chosen resting-to-pulse times, the applied current density, and elucidate that three-dimensional cathode materials yield higher capacities compared to two-dimensional ones. By implication, the pulse discharging mode ensures better supply with dissolved oxygen within the cathode. The higher amount of dissolved oxygen accumulated during the resting period after a current pulse is essential to form more of the discharge product, i.e., the metal oxide sodium superoxide. Interestingly, we show for the first time that the superoxide is deposited in a very unusual form of stacked and highly oriented crystal layers. Our findings on the pulse discharging can be transferred to other metal-oxygen battery systems and might assist in achieving their full potential regarding practical energy density.